Hot Filament CVD epitaxy of 3C-SiC on 6H and 3C-SiC substrates. (12th January 2017) - Hens, Philip; Brow, Ryan; Robinson, Hannah; Van Zeghbroeck, Bart
ABSTRACT: For the first time, we are reporting the growth of high quality single crystalline 3C-SiC epitaxially on hexagonal silicon carbide substrates using Hot Filament Chemical Vapor Deposition (HF-CVD) on full 4" wafers. Rocking curve X-Ray diffraction (XRD) measurements resulted in a full width at half maximum (FWHM) as low as 88 arcsec for a 40 µm thick layer. We achieved this quality using a carefully optimized process making use of the additional degrees of freedom the hot filaments create. The filaments allow for precursor pre-cracking and a tuning of the vertical thermal gradient, which creates an improved thermal field compared to conventional Chemical Vapor Deposition. Growth rates of up to 8 µm/h were achieved with standard silane and propane chemistry, and further increased to 20 µm/h with chlorinated chemistry. The use of silicon carbide substrates promises superior layer quality compared to silicon substrates due to their better match in lattice parameters and thermal expansion coefficients. High resolution scanning electron microscopy, X-Ray rocking measurements, and micro-Raman allow us to assess the crystalline quality of our material and to compare it to layers grown on low-cost silicon substrates. Hall measurements reveal a linear increase of the charge carrier density in the material with the flow of nitrogen gas as a dopant. Electron densities above 10 -18 cm -3 have been reached.